Το Έπος του Ελ Σιντ: εισαγωγή-πρωτότυπο κείμενο-μετάφραση-σχόλια - Ιωάννης Κιορίδης; Στέργιος Ντέρτσας; Αλμπέρτο Μοντανέρ (Romi, 2019)
This book is the first Greek translation, directly from the original Spanish text and with full commentary, of the Song of El Cid (Cantar de mio Cid), a leading medieval epic poem from Castile in the early 13th century and one of the most important works of world literature. It therefore fills an important gap in Greek bibliography and makes this work accessible to the Greek academic, scientific, and general public.